BETWEEN GIBAH AND FITNAH : (ANALYSIS OF GOSSIP SHOWS ON TV IN HADITH PERSPECTIVE) - Munzir, Muhammad; Ismail, Muhammad; Aksa Muhammad Nawawi, (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2025)
Gossip is an activity that will only lead to two things, namely gibah or fitnah so that this will greatly impact the comfort of social life relationships, even so, gossip remains something that is favoured by every line in society, even in the era of contemporary life today gossip is used as an event on TV media or social media in general. This research intends to explore the hadiths about gossip, which are then connected to the gossip programmes broadcast on TV today. Therefore, in this research, a qualitative method is used, in which the traditions related to gossip will be analysed using descriptive analysis. The results of the study show that gossip is an activity in which a person talks about the negative things about a person, and that he is not happy if other people spread it. Gossip is very impactful on the order of social life because gossip can damage a person's reputation, can trigger social conflicts that can even make social relations disharmonious and full of suspicion between one person and another.